Community radio town Maracaibo. Self-sustainable? (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2013)
The purpose of the given work-study is to examine the economic auto sustainability of the community radios in the township of Maracaibo, based on the contribution and principles of ALER (2008) and Lamas (2003). In this case the investigation was managed in a descriptive and fieldwork matter, a semi-structured interview was applied to every community radio director through CONATEL Maracaibo, by which a population census was established. The data collected was organized into categories according to Strauss and Corbin (2002). The results show the necessity of more actions to achieve the sustainability in time. As a result the community radios have been able to last and fortify economically throughout time, due to the combined economic actions related primarily by the participation of the community social actors linked to the media, nevertheless, the community dynamics require the boost of cultural entrepreneurship, productive activities, among others in order to contribute in the progress of the radios' economic auto sustainability.
Keywords: economic strategies; sustainability; actions; actions to fortify community radios